Hiding Filthy Lucre in Plain Sight: Theory and Identification of Business-Based Money Laundering - Keith E. Maskus; Alessandro Peri; Anna Rubinchik (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Proceeds from illicit activities percolate into the legal economy through several channels. We exploit international regulations targeting money laundering via the financial sector to identify the flows of “dirty money” into legitimate establishments: business-based money laundering (BBML). Our variant of the monopolistic competition model embeds a drug cartel that channels illicit proceeds into an offshore financial investment and into BBML. Tighter regulations in one channel increase the flow in the other. We use a research design that links U.S. county business activity to the evolution of anti-money-laundering regulations in Caribbean jurisdictions to provide the first empirical evidence of the phenomenon.
Keywords: F30; K40; G28; H00; D58; 330; money laundering; business establishment; Panama Papers; anti-money-laundering regulations; monopolistic competition